Chinese women in industrial home-based sub-contracting in the garment industry in Kuala Lumpur: neither valued nor costed - Lee Lee LOH-LUDHER, (Universiti Kebangsaan Malaysia, 2003)
This article examines the circumstances leading to fifty-five married Chinese women’s withdrawal from participation in the formal sector to enter the informal sector specifically in home-based sub-contracting work. These women sub-contract from the garment makers to sew, cut and embroider at home while caring for their family. The article also discusses if the efforts of these home-based sub-contractors are costed and valued by the factories, their families and themselves. The home-based sub-contractors provide an industrial reserve army that is truly disposable, flexible and cheap. They create an informal sector within the formal structure giving the best of both worlds for the extraction of surplus by the garment makers. However, although home-based sub-contractors offer tremendous advantages to the garment industry to ensure its competitiveness and flexibility, the industry, evidently, does not value them nor are they costed. Even the husbands fail to value these women’s contribution to family well-being.